Antarctic climate response in Last-Interglacial simulations using the Community Earth System Model (CESM2) - Berdahl, Mira; Leguy, Gunter R.; Lipscomb, William H.; Otto-Bliesner, Bette L.; Brady, Esther C.; Tomas, Robert A.; Urban, Nathan M.; Miller, Ian; Morgan, Harriet; Steig, Eric J. (2024)
We examine results from two transient modelling experiments that simulate the Last Interglacial period (LIG) using the state-of-the-art Community Earth System Model (CESM2), with a focus on climate and ocean changes relevant to the possible collapse of the Antarctic ice sheet. The experiments simulate the early millennia of the LIG warm period using orbital forcing, greenhouse gas concentrations and vegetation appropriate for 127 ka; in the first case ( 127 ka ) no other changes are made; in the second case ( 127 kaFW ), we include a 0.2 Sv freshwater forcing in the North Atlantic. Both are compared with a pre-industrial control simulation ( piControl ). In the 127 ka simulation, the global average temperature is only marginally warmer (0.004 °C) than in the piControl . When freshwater forcing is added ( 127 kaFW ), there is surface cooling in the NH and warming in the SH, consistent with the bipolar seesaw effect. Near the Antarctic ice sheet, the 127 ka simulation generates notable ocean warming (up to 0.4 °C) at depths below 200 m compared to the piControl . In contrast, the addition of freshwater in the North Atlantic in the 127 kaFW run results in a multi-millennial sustained cooling in the subsurface ocean near the Antarctic ice sheet. We explore the physical processes that lead to this new result and discuss implications for climate forcing of Antarctic ice sheet mass loss during the LIG.